2007
DOI: 10.1007/s11064-007-9480-0
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones affect the Level and Activity of Nitric Oxide Synthase in Rat Cerebral Cortex during Postnatal Development

Abstract: The effects of thyroid hormones (TH) on the enzyme level and activity of neuronal nitric oxide synthase (nNOS) were studied in the rat cerebral cortex during postnatal life. As revealed by arginine/citrulline conversion assay and Western blot analysis of the homogenate of the parietal cortex T4 significantly increased nNOS activity and nNOS protein level to 153 +/- 25% and to 178 +/- 20%, respectively. In contrast, 6-n-propyl-2-thyouracil (PTU) decreased nNOS activity and nNOS level to 45 +/- 10% and to 19 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…In contrast, PTU, which is a selective inhibitor of thyroid gland cell function, retards the developmental process, and decreases the density and intensity of nNOS-IR granule cell axon fibers, together with induction of the diminution of the cGMP level and abolishment of the cGMP-IR material in the cerebellum. Recently, similar to present findings, a positive correlation was observed between TH level and nNOS expression in the cerebral cortex at the same interval of postnatal ages [23]. In contrast, an inverse ratio was detected in 14- to 18-day-old embryos during maternal hypothyroidism [22], suggesting that the direction of nNOS regulation by TH is time dependent and may occur through different mechanisms during development.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, PTU, which is a selective inhibitor of thyroid gland cell function, retards the developmental process, and decreases the density and intensity of nNOS-IR granule cell axon fibers, together with induction of the diminution of the cGMP level and abolishment of the cGMP-IR material in the cerebellum. Recently, similar to present findings, a positive correlation was observed between TH level and nNOS expression in the cerebral cortex at the same interval of postnatal ages [23]. In contrast, an inverse ratio was detected in 14- to 18-day-old embryos during maternal hypothyroidism [22], suggesting that the direction of nNOS regulation by TH is time dependent and may occur through different mechanisms during development.…”
Section: Discussionsupporting
confidence: 88%
“…The minimum level which can be detected by the method is 4 ng/l for T 3 and 1.8 µg/l for T 4 . Details of the measurement description can be found in our recent publication [23]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between nNOS and poor survival of neurons and thyroid hormone deprivation has also been suggested 67. It has been shown that even a moderate and transient decrease in maternal thyroxine significantly increases nNOS expression, which is reversible by hormone replacement 67,72. In contrast, another report showed that propylthiouracil (PTU)-treated animals exhibited reduced NOS activity that could be rescued by T4 administration 72.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major players in this process is a neurotransmitter known as nitric oxide (NO) produced by an enzyme neuronal nitric oxide synthase (nNOS) expressed in newly generated neurons. Although nNOS expression is modulated by steroid and THs during postnatal development (14,15), its modulation by TH during the embryonic period lacks definite evidence. Therefore, the present study has been performed to understand the effect of maternal TH deficiency on the expression of nNOS, and its consequent impact on generation and survival of neocortical neurons.…”
mentioning
confidence: 99%